Evaluating the trajectory of growth in the pharmaceuticals market : a case of Karnavati Chemist Store in India - Thomas, Sujo; Gandhi, Pervin; Susmita, Suggala (London : SAGE Publications Pvt. Ltd, 2016)
Karnavati Chemist Store, a popular store in the city of Ahmedabad, a successful entrepreneurial venture is at the crossroads. The case is an in-depth analysis of a range of growth options for this stand-alone store, known amongst its loyal customers for its ideal services in the heart of the city. The journey of the store, factors contributing to its sustainability and growth in the era of upcoming organized retail store formats throw light on a series of facets contributing to the success quotient of the store. Karnavati Chemist Store wanting to ride the growth wave had wished to extrapolate their learnings and experiences for their future stores, an inevitable decision under such conditions. Franchising seemed a good option, provision for financing had also been apportioned and a need for slight tweaking of the distribution system to ensure a flawless delivery system had been expressed. The case is an insightful explanation, with logical arguments and discussions of the various store formats, aspects contributing to the success to determine the new journey embarked on to become a prominent player in pharmacy retailing in the years ahead.
Originally published in Thomas, S., Gandhi, P., & Susmita, S. (2016). Evaluating the trajectory of growth in the pharmaceuticals market: A case of Karnavati Chemist Store in India. South Asian Journal of Business and Management Cases, 5(2) 209-220. DOI:.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Karnavati Chemist Store -- Case studies; Industrial management -- India -- Case studies; Retail trade -- India -- Case studies